Utilization of fermented water hyacinth (Eichornia. crassipes) meal using cow rumen liquor in diets on growth of Pangasius (P. hypophpthalmus) fingerling - Dani Yosi R.Sibarani; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted for 56 days from June to August 2017. The aim of this research is todetermine the number of water hyacinth leaf meal fermented using cow rumen liquo in diets on growth of Pangasius (P. hypohthalmus).This study used completely randomized design (CRD) with five treatments and three replications. The fish used in this research with  in2g of weight.Fish were reared in 1m3 cages with the stocking density of 25 fish/cage. Feeding trials were replacing with soybean meal with fermented water hyacinth  applied to P0 (0%), P1(30%), P2 (40%), P3 (50%) and P4 (60%) for 35% of protein content.The result showed that fermentedwater hyacinth (P<0.05) on give growth, and feed efficiency of P.hypophthalmus retention. Replacement 40% of water hyacinth fermentatied highest spesific growth rate 3,60%, feed eficiency 41,01%, feed digestibility81,38 %. Key word : Fermentation, Pangasius hypophthalmus, Rumen liquor, Water hyacinth